1994
DOI: 10.1148/radiology.190.2.8284404
|View full text |Cite
|
Sign up to set email alerts
|

Suspicious breast lesions: MR imaging with radiologic-pathologic correlation.

Abstract: There is an overlap in the signal intensity characteristics and enhancement profiles of benign and malignant lesions. However, border characteristics, internal architecture, enhancement characteristics, and the presence of multiple tiny associated cysts may be important clues to lesion identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
238
0
15

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 432 publications
(259 citation statements)
references
References 0 publications
6
238
0
15
Order By: Relevance
“…Some investigators who have concentrated on T1-weighted, time-signal intensity characteristics of gadolinium enhancement report very high specificities (83%-97%) (6,7,(17)(18)(19), but others have seen no significant difference between benign and malignant abnormalities (2,5,20). Investigators who have tried to directly compare the use of contrast enhancement kinetics to the use of architectural features have found architectural features to be superior to quantitative kinetic indices alone (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some investigators who have concentrated on T1-weighted, time-signal intensity characteristics of gadolinium enhancement report very high specificities (83%-97%) (6,7,(17)(18)(19), but others have seen no significant difference between benign and malignant abnormalities (2,5,20). Investigators who have tried to directly compare the use of contrast enhancement kinetics to the use of architectural features have found architectural features to be superior to quantitative kinetic indices alone (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…However, both high spatial resolution architectural imaging data and high temporal resolution contrast kinetic data could ideally be obtained in a single MR examination, and perhaps used in combination for greater diagnostic accuracy. Some investigators (21) have been evaluating single pulse sequences to try to allow this occurrence, but their spatial resolution does not yet equal that of studies designed to maximize spatial resolution (2)(3)(4)22,23). Although pulse sequences have been reported that can obtain both high spatial and high temporal resolution concurrently, their efficacy has not yet been clinically tested (24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8] DiŠerences in the characteristics of MR enhancement between benign and malignant lesions are believed to re‰ect diŠerences in vascularity, vessel permeability, and extracellular diŠusion space. In addition, several morphologic characteristics and kinetic patterns on MR imaging in breast carcinoma are primarily explained by the histological structures of the lesions, [9][10][11] such as centralˆbrosis, central necrosis, marginalˆbrosis, and the degree of tumor angiogenesis.…”
Section: Introductionmentioning
confidence: 99%